Mass Multiplication of Dendrocalamus hamiltonii Munroa Critical Evaluation - Sharma, D. P. (Indian Forester, 1986)
Performance of one-node culm cuttings with preformed roots at (i) pimary-branch bases, and (ii) culm nodes was evaluated. They were taken from Under one-year-old juvenile (actively branched) and adult culms respectively and planted in March. In the first case, out of 391 cuttings 323 survived, of which 301 produced complete plants, ready for outplanting, in one year. In a particular culm the cuttings that died belong to the distal region in a basipetal order. The new plant starts from a branch. In the second case, out of 603 cuttings only 104 produced complete plants in the first year. The number rose to 309 in the second year, but the remaining 294 cuttings died or ended blindly. The new plant starts from a bud.